2016
DOI: 10.1159/000446759
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Intracranial Response to Osimertinib in a Patient with Epidermal Growth Factor Receptor T790M-Positive Adenocarcinoma of the Lung

Abstract: Background: Osimertinib (AZD9291, Tagrisso) is a potent, irreversible third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI). Case Report: Our report demonstrates that osimertinib is able to inhibit the growth of a radiotherapy- and surgery-refractory EGFR T790M-positive brain metastasis in a patient with lung adenocarcinoma. Conclusion: These data show that re-biopsy in EGFR-mutated non-small cell lung cancer patients with acquired TKI resistance should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…There are currently limited data on the effectiveness of osimertinib alone for patients with progressing brain metastases. Some case reports have demonstrated that the clinical responses achieved on osimertinib may obviate the need for whole‐brain radiation in some patients . The phase I BLOOM study studied the effects of osimertinib 160 mg daily on 20 patients with advanced NSCLC who had progressed on prior EGFR TKIs and had confirmed leptomeningeal disease by cerebrospinal fluid cytology, but the study did not focus on parenchymal metastases .…”
Section: Discussionmentioning
confidence: 99%
“…There are currently limited data on the effectiveness of osimertinib alone for patients with progressing brain metastases. Some case reports have demonstrated that the clinical responses achieved on osimertinib may obviate the need for whole‐brain radiation in some patients . The phase I BLOOM study studied the effects of osimertinib 160 mg daily on 20 patients with advanced NSCLC who had progressed on prior EGFR TKIs and had confirmed leptomeningeal disease by cerebrospinal fluid cytology, but the study did not focus on parenchymal metastases .…”
Section: Discussionmentioning
confidence: 99%
“…For the 2017 update (Version 4), the NCCN panel now also recommends osimertinib (category 1) for patients with T790M who have brain metastases. 37,[164][165][166] Data suggest that an afatinib/cetuximab regimen may be useful for patients whose disease has progressed after receiving EGFR TKI therapy and chemotherapy. 238 Patients with T790M-positive and T790M-negative tumors had a similar response rate to an afatinib/cetuximab regimen (32% vs 25%; P=.341).…”
Section: Second-line and Beyond (Subsequent) Systemic Therapymentioning
confidence: 99%
“…This PFS benefit was true even for the over 30% of patients with asymptomatic BrM at enrollment with a hazard ratio of 0.32 [53••]. Intracranial response has also been reported in patients with BrM as well as patients with leptomeningeal disease [5456]. For patients with T790M, either primary or secondary, we favor the use of osimertinib for the use of EGFRact+ BrM.…”
Section: Systemic Therapymentioning
confidence: 93%